Alcohol consumption among the member states of the European Union in relationship to taxation - Horáková, Monika; Bejtkovský, Jiří; Barešová, Petra; Urbánek, Tomáš (Adiktologie, 2020)
BACKGROUND: Alcohol is one of the main economic commodities, which represents a significant amount of government tax revenues and consumer spending. Alcohol is associated with health, economic and social impacts on people ́s lives. The task of national governments is not only to address the effects of alcohol but also to address the causes that help eliminate alcohol dependence. Tools that governments can use include price policy through alcohol taxation rates (excise duties, VAT), reduce accessibility to purchase alcohol beverages, raising awareness of the harmful effects of drinking for driving or among teenagers, etc. AIM: The main goal of the research was to examine dependencies between the amount of alcohol consumption and VAT rate for alcohol in EU Member States from 2010–2018. Selected data for the years 2010, 2012, 2014, 2016 and 2018 correspond to the published reports of the European Commission and the OECD. DESIGN AND MEASUREMENTS (METHODS): Secondary data for the research were obtained from available international statistics, which include databases from European Commission, the OECD, the WHO and Eurostat. Statistical methods as Kruskall-Wallis test were used for data analysis. SAMPLE: The sample consisted of complete data of 23 European Union Member States. RESULTS: The results of the research did not show a significant difference in the median alcohol consumption in the period 2010–2018 in the measured 23 EU countries. While the study of the dependence of VAT and alcohol consumption has shown a significant dependence. The highest base of alcohol consumption was recorded in Lithuania, Austria and Estonia, while the lowest base was recorded in Italy and Sweden. The VAT rate has been shown to have the highest impact on reducing alcohol consumption in Lithuania, Greece and Estonia. CONCLUSIONS: Among other things, it is possible to formulate a clear and concrete conclusion that increasing VAT on alcohol beverages will reduce the amount of alcohol consumption. This research finding would undoubtedly support the field of population health and prevention of alcoholism, but would have a negative effect on the economic functioning of individual EU Member States.